A dependencies satisfaction tool to support the cost oriented configuration of industrial products in the conceptual design stage. Issue 6 (2nd November 2018) - Peruzzini, Margherita; Pistacchi, Mauro; Savoretti, Andrea; Mandolini, Marco; Raffaeli, Roberto
ABSTRACT: Sustainability and cost optimization are actually the main drivers of product and system design in modern companies. However, cost assessments are usually carried out at the end of the design process to check the validity of the decisions already taken. Therefore, when targets are not achieved, numerous time-consuming iteration loops are necessary to optimize the initial solution. The paper situates in a research aimed at merging functional-based and design-to-cost approaches to propose a CAD-based platform able to assess new product variants from the earliest stages by configuring and assessing feasible design solutions. In particular, an approach is proposed for dealing with dependencies among design parameters in order to support the designer in a rapid definition of valid solutions and optimise them. The approach is described and then applied on an industrial test case, a bridge-crane design process. GRAPHICAL ABSTRACT: